PARTISIPASI PEKERJA DALAM SERIKAT PEKERJA - Hamong Santoso; Indi Djastuti (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2011)
This research aims to evaluation performance of agriculture extension agent and estimates expense of transaction needed to design revitalization scenario of counseling institute. This research applies primary data collected through interviews with respondent and key-persons. 200 farmers and 30 Agriculture extension agents taken as a sample with multistage sampling. The descriptive Statistics applied to depict responder profile, extension agent performance, and condition of the institution of counseling. A transaction cost will be applied to estimate the value of the expense of the transaction needed to design revitalization scenarios of the institution of counseling. The result of the research indicates that the behavior of farming in the research area has not been efficient, so that there is an opportunity to optimize farm production through counseling.